Aging and Popular Music in Europe. - Gardner, Abigail; Jennings, Ros. (Milton : Routledge, 2019)
Opening up the dialogue between popular music studies and aging studies, this book offers a major exploration of age and popular music across Europe. Using a variety of methods to illustrate how age within popular music is contingent and compelling, the volume explores how it provokes curation and devotion across a variety of sites and artists who record in several European languages, and genres including waltz music, electronica, pop, folk, rap, and the French chanson.' Visiting the many ways in which age is problematized, revered, and performed within Europe in relation to popular music, case studies analyze: French touring shows of popular music stars from the 1960s; Andr Rieu's annual Vrijthof concerts in the Netherlands; Kraftwerk and Bjrk's appearances at renowned art museums as curated objects; queer approaches to popular music space and time; British folk music inheritances; pan-European strategies of stardom and career longevity; and inheritance and post-colonial hauntings of race and identity. The book works with the notion of travelling, across borders, genres, sexualities, and media, highlighting the visibility of the aging body across a variety of European sites in order to establish popular music through the lens of age as a positive methodology with which to approach popular music cultures, and to offer a counter-narrative to age as decline. This book will appeal to scholars of popular music, popular culture, media studies, cultural studies, aging studies, and cultural gerontology.
OCLC-licensed vendor bibliographic record.
Keywords: Popular music -- Social aspects -- Europe; Older musicians -- Europe; MUSIC -- Genres & Styles -- Pop Vocal; MUSIC -- Ethnomusicology; SOCIAL SCIENCE -- Gerontology